Magnetoelasticidade e comportamento crítlco em cadeias de ising - Ota, André Tsutomu; Salinas, Silvio Roberto de Azevedo (Semina: Ciências Exatas e Tecnológicas, 2004)
We consider two distinct ways of introducing elastic degrees of freedom in the one-dimensional Ising model. Taking into account the average effect of elastic vibrations, the effective spin Hamiltonian in the pressure ensemble diplays long-rang interactions which give rise to a first-order phase transition. However, local fluctuation of the crystalline positions lead to an effective spin Hamiltonian with short-range interactions and without any thermodynamic anomaly in one dimension.